Grounded theory for transition to and adoption of agile software development - Gandomani, Taghi Javdani (2014)
Successful migration from traditional software development methods to Agile methods, as an organizational mutation, requires enough understanding of Agile transformation process and its related issues. Reviewing the literature revealed that software companies are struggling with many challenges during Agile transition process. However, there was no large-scale research study to elucidate various aspects and dimensions of the transition process. Also, less effort has been devoted to investigate the whole transition process. A Grounded Theory study with participation of 49 Agile experts from 13 different countries, mostly from USA and West Europe countries, and some from Asia and Australia, has been carried out to investigate the realities of Agile transformation. Adopted research methodology provided a systematic approach to discover various aspect of the transformation through a multi-level data analysis including open coding, selective coding, and theoretical coding. Following a high disciplined approach, various concepts and categories have been identified and finally, the main concern of the participants, known as core category, has been discovered as the theory of Agile transition and adoption comprising four major parts: (1) Agile Transition Key Prerequisites, (2) Agile Transition Challenges, (3) Agile Transition Facilitators, and (4) Agile Transition and Adoption Framework. This study discovered the most important prerequisites that software companies need to provide before starting their transition to Agile approach including having convincing reason for change, defining business values, initial training, etc. Software companies have to do a preparation phase to provide these prerequisites before starting Agile transformation. It also identified the major challenges that software teams and companies are facing with when moving to Agile, including negative human aspects, inadequate and dysfunctional training, technical challenges, etc. These challenges have different roots and acts as impediments to the change. Also, this study discovered various change facilitators, including training, getting buy-in from practitioners, good coaching service, etc. Providing these facilitators help software teams to deal with the transformation challenges and increase chance of success. Finally, it proposed a substantive framework for transitioning to Agile approach. The proposed framework has particular features, discipline, and activities which promise usefulness for Agile transformation process in software companies regardless of size and project type. This framework particularly aims to promote sustainable change and being Agile instead of doing Agile. In general, this study developed the theory of Agile transition and adoption and discovered various aspects of the transformation. The findings of this study will serve to inform all software practitioners about transitioning to Agile software development.